MOTIVASI SWISS MENCABUT PAGU NILAI MATA UANG FRANC TERHADAP EURO 2015 - Hutagalung, Karlos Dominggo; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
After the crisis hit Europe in 2009, there was a massive Euro capital movement to Swiss causing the overvaluation of the Franc against the Euro which threatened the Swiss economic growth, because Swiss is an exporter country. To save the economy of Swiss, Swiss National Bank announced to set minimum exchange rate at CHF 1.20 per euro in 2011. The policy was successfully boosting the economic growth rate, and preventing the threat to the Swiss export sector from 2011-2014, but without any domestic financial crisis and prior notice, on 15 January 2015, Swiss announced to unpeg the Euro and deliberately weakened its economic growth projection from 1,8% to 0,5% in 2015. This policy was taken after swiss announced its commitment to keep the peg on December 2014 media news conference of Swiss National Bank. So the question arises about why the Swiss unpegged the Franc currency against the Euro in 2015.This research is using liberalism perspective, Liberals believe that states can work together mutually benefited and all the policies they made ultimately to ascertain free trade can work properly. The author used price specie flow mechanism theory by David Hume with the level of the nation-state analysis. This theory emphasize that the goal of monetary policy is the economic balance and stability. This research applying qualitative methods and library research, with the sources are from books, journals, official publications, articles, news, and internet.This research shows that Swiss unpegged the Franc-Euro currency to prevent the risk of domestic economic instability due to the failure of the European Union to overcome the Euro crisis. In the ongoing situation of the European economic crisis and the pegging policy creating an economic bubble that could be ruptured as triggered by hyperinflation.Keyword: Peg, Monetary Policy , Currency, Overvaluation, Economic Growth